2009
DOI: 10.1007/s00216-009-3338-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biochemical changes in lactovegetarian urine using 1H NMR spectroscopy and pattern recognition

Abstract: A vegetarian diet has been demonstrated to have a profound influence on human metabolism as well as to aid the prevention of several chronic diseases relative to an omnivorous diet. However, there have been no systematic metabolomic studies on all of the biochemical changes induced in human subjects by long-term vegetarianism. In this study, (1)H NMR spectroscopy in combination with multivariate statistical analysis was applied to explore the variability in the metabolic urinary profiles of healthy populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
51
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 51 publications
10
51
1
Order By: Relevance
“…On the other hand, gut microbiota of omnivores produced higher levels of TMAO because of the increased ingestion of L-carnitine mainly from red meat. Similar data have been previously shown by Xu et al 30 as lactovegetarians presented decreased urinary concentration of TMAO. Stella et al 31 reported high urinary TMAO excretion in response to meat intake.…”
Section: Tmao and The Dietsupporting
confidence: 90%
“…On the other hand, gut microbiota of omnivores produced higher levels of TMAO because of the increased ingestion of L-carnitine mainly from red meat. Similar data have been previously shown by Xu et al 30 as lactovegetarians presented decreased urinary concentration of TMAO. Stella et al 31 reported high urinary TMAO excretion in response to meat intake.…”
Section: Tmao and The Dietsupporting
confidence: 90%
“…Furthermore, metabolomics can highlight the metabolites and metabolic pathways influenced by diet, which could be further assessed in prospective studies of disease outcomes with the use of mediation analysis to provide insights into the mechanisms that may be driving dietary pattern-disease relations. Although a number of small studies have evaluated individual food item associations with blood metabolite concentrations, to our knowledge, very few have evaluated dietary patterns, and, of these, most have used data-driven approaches with small samples (3,(29)(30)(31). Our 2 purposes were as follows: 1) to identify metabolites correlated with 4 dietary patterns and their components [with the HEI-2010, the Alternate Mediterranean Diet Score (aMED), the HDI, and the Baltic Sea Diet (BSD)], and 2) to gain insights into the potential biological mechanisms influenced by diet quality.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, population-based studies have shown marked differences in metabolic profiles within and between populations that reflect dietary differences (16,17). A number of metabolic profiling studies have been undertaken to assess the metabolic phenotype of humans due to their dietary pattern (18,19). Moreover, a metabolomic approach has been proposed to evaluate the intricate relationship between nutrition and health (20).…”
Section: Introductionmentioning
confidence: 99%